Refining the Distributional Inclusion Hypothesis for Unsupervised Hypernym Identification - Ludovica Pannitto; Lavinia Salicchi; Alessandro Lenci (IJCoL)
Several unsupervised methods for hypernym detection have been investigated in distributional semantics. Here we present a new approach based on a smoothed version of the distributional inclusion hypothesis. The new method is able to improve hypernym detection after testing on the BLESS dataset.